Operators Preserving Primitivity for Matrix Pairs - Beasley, LeRoy B.; Guterman, Alexander E. (Matrix Methods: Theory, Algorithms And Applications, 2010)
The following sections are included: Introduction Preliminaries Matrices over the binary Boolean semiring Matrices over antinegative semirings without zero divisors References